1976
DOI: 10.1007/bf00256134
|View full text |Cite
|
Sign up to set email alerts
|

Fasting urine excretion of magnesium, calcium, and sodium in patients with renal calcium stones

Abstract: Urine excretion of magnesium (Mg), calcium (Ca) and sodium(Na) was studied in patients with renal Ca stones having normal kidney function (n= 60), and in matched controls (n= 60), on a free diet following an overnight fasting period. In some formers, Mg was lower than in normals, whereas Ca was unusually high resulting in a significantly higher molar Ca/Mg ratio (p less than 0.001). 2. In 3 out of 4 stone groups Na excretion was significantly elevated because of reduced tubular reabsorption. In normals, fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…The relative stability of oxalate and citrate concentrations thus indicates the close correlation between their elimination and urinary output which is the result of a passive phenomenon of tubular reabsorption [3,5,7]. Conversely, marked circadian oscillations in urine calcium and magnesium levels are indicative of excretions which are less dependent upon diuresis, because these cations undergo a process of active distal tubular reabsorption [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…The relative stability of oxalate and citrate concentrations thus indicates the close correlation between their elimination and urinary output which is the result of a passive phenomenon of tubular reabsorption [3,5,7]. Conversely, marked circadian oscillations in urine calcium and magnesium levels are indicative of excretions which are less dependent upon diuresis, because these cations undergo a process of active distal tubular reabsorption [4,9].…”
Section: Discussionmentioning
confidence: 99%
“…In general, stone formers appear to have a magnesium excretion not different from that of healthy nonstone forming subjects (1 1,20,26, 32, 40,47,48,52,53). In some studies, however, stone formers were reported to have a low urinary magnesium excretion, either in comparison with controls not matched for age and sex (19, 29, 34), or in comparison with an adequate matched control group (44,50).…”
Section: Magnesium Metabolism In Renal Stone Diseasementioning
confidence: 99%
“…Most authors report high percentages in hypercalciuric calcium oxalate stone patients (30%), whereas others also cite lower percentages (7, 9, 12). An increase as well as a decrease in the sodium excretion of stone patients is reported in the literature (14,15). Whereas magnesium values In our hospital we have therefore determined quantitatively, besides urine and serum investiga tions, the concentrations of some important ele ments in kidney and muscle tissue.…”
mentioning
confidence: 99%